Physicochemical Properties of Experimental Resin-Based Materials Containing Fluoridated Calcium Phosphates - Feitosa, Victor P.; Pinheiro, Levy S.; Moura, Maria Elisa M.; De-Paula, Diego M.; Alves, Adyson H.; Rodrigues, Lidiany Karla; Sauro, Salvatore (Frontiers in Materials, 2020)
The aim of this study was to evaluate the physicochemical properties of experimental adhesives containing tailored fluoridated calcium phosphate fillers. Five experimental resins were formulated, one contained no calcium phosphate filler (Control) and the other four resins contained 40wt% of calcium phosphate fillers doped with increasing concentration of fluoride: adhesives CaP (no fluoride), CaP-2F (2wt% F), CaP-4F (4wt% F) and CaP-8F (8wt% F). Resin specimens were prepared for three-point bending test to evaluate the elastic modulus (E) and flexural strength (FS) at 24h and after 2 months of water storage. Disk-shaped specimens were prepared to analyze the water sorption (Ws) according to ISO 4049. The degree of conversion (DC) of the tested resins was also assessed through FTIR. Statistical analysis was performed with ANOVA and Tukey’s test (p<0.05). The addition of F-CaP particles at 0 and 2wt% fluoride had no effect on the DC (p>0.05) compared to the filler-free resin. However, these same experimental resins showed the highest E after water storage. All resins had a significant reduction of the FS after water storage (p<0.001), but at lower percentage rate for those experimental resins containing fluoride-free CaP or fluoride-doped CaP-2F.. These latter experimental resins achieved similar Ws to control filler-free resin. Conversely, those resins containing 4wt% or and 8wt% fluoride-doped CaP promoted had a significant Ws increase (p<0.05). In conclusion, the incorporation of calcium phosphate particles without fluoride and or with 2wt% fluoride may represent be a promising strategy to generate adhesive resins with specific physicochemical properties. Fluoride incorporation in CaP fillers for dental resin adhesive should be performed at low concentrations in order to avoid excessive water sorption and decrease of polymerization.